ANALISIS AKUISISI PT. INDOSIAR KARYA MEDIA TBK OLEH PT. SURYA CITRA MEDIA TBK DI TINJAU DARI PERSPEKTIF HUKUM PERSAINGAN INDONESIA - , FEBRI YUDHA PRATAMA, Prof. M. Hawin, S.H., LL.M., Ph. D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The development of private enterprises today are colored by various forms of policies that are less precise ruler, so the market becomes distorted. On the other hand, most of the development of private enterprise is in fact a manifestation of the condition of unhealthy competition or unfair, including in the field of television broadcasting. A large number of television stations in the broadcasting industry will cause the level of competition among television stations are each trying to win the competition because of the demands of business. The orientation of the broadcast media at the moment is looking for maximum profit with pragmatic without seeing the impact that can be caused. Instead of for-profit private television action that is by doing takeovers (acquisitions) Other private companies, so the occurrence of market share in the same field that is broadcasting. This is done by PT. Surya Citra Media Tbk acquired PT. Indosiar Karya Media Tbk. This study aims to determine how the acquisition of PT. Indosiar Karya Media Tbk by PT. Surya Citra Media Tbk on the review of Pasal 28 (2) jo Pasal 17 (2) UU No. 5/1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. and How Application of rule of reason in the acquisition of PT. Indosiar Karya Media Tbk by PT. Surya Citra Media Tbk, which violates the principle of diversity of ownership and diversity of content in the Law. 32 Year 2002 on Broadcasting. This research is a normative legal research with emphasis on the research literature will be more review of secondary data, as for the analysis of qualitative research conducted in the outline data in a systematic form of writing, making it easier to provide for further interpretation of the conclusions drawn in order to answer the research problems. The results of the discussion are: (1) acquisition of PT. Indosiar Karya Media Tbk by PT. Surya Citra Media Tbk not violate Pasal 28 (2) jo Pasal 17 (2) of Law. 5 Year 1999 (2) in the implementation, KPPU only assesses the problems of acquisition of the normative perspective of Antitrust Law and PP No. 57/2010 by prioritizing economic and business interests. So the principle of the rule of reason from the sociological aspect doesn't really apply in by the KPPU.